Cross-sectional and longitudinal associations between serum uric acid and endothelial function in subjects with treated hypertension. (1st December 2018) - Tanaka, Atsushi; Kawaguchi, Atsushi; Tomiyama, Hirofumi; Ishizu, Tomoko; Matsumoto, Chisa; Higashi, Yukihito; Takase, Bonpei; Suzuki, Toru; Ueda, Shinichiro; Yamazaki, Tsutomu; Furumoto, Tomoo; Kario, Kazuomi; et al.
Abstract: Objectives: The endothelial dysfunction-arterial stiffness-atherosclerosis continuum plays an important pathophysiological role in hypertension. The aim of this study was to investigate the cross-sectional association between serum uric acid (SUA) and vascular markers related to this continuum, and to assess the longitudinal association between SUA and endothelial function that represents the initial step of the continuum. Methods: We evaluated the baseline associations between SUA levels and vascular markers that included flow-mediated vasodilatation (FMD), brachial-ankle pulse wave velocity (baPWV), and common carotid artery intima-media thickness (CCA-IMT) in 648 subjects receiving antihypertensive treatment. The longitudinal association between baseline SUA levels and FMD measured at 1.5 and 3 yr of follow-up was also investigated. Results: At baseline, modest, but significant correlations were observed between SUA and FMD in females ( r  = −0.171), baPWV in males with SUA >368.78 μmol/L ( r  = −0.122) and in females with a SUA level ≤ 362.83 μmol/L ( r  = 0.217), mean CCA-IMT in females with a SUA level ≤ 333.09 μmol/L ( r  = 0.139), and max CCA-IMT in females with SUA level ≤ 333.09 μmol/L ( r  = 0.138). A longitudinal association between SUA and FMD was less observed in males. In females, the baseline SUA was associated significantly with FMD values at 1.5 yr ( r  = −0.211), and SUA levels >237.92 μmol/L were associated significantly and independently with FMD values at 3 yr ( r  = −0.166). Conclusions: Lower SUA levels were associated with better vascular markers of the continuum, especially in females. Furthermore, we observed a longitudinal association between SUA and endothelial function, suggesting SUA level may be a potential marker of the continuum in hypertension. Highlights: No significant association between SUA and FMD in hypertensive males was found. In hypertensive females, SUA were associated negatively with FMD up to 3 yr. Lower SUA levels associated with better endothelial function, especially in females. SUA may be a useful marker of the atherosclerotic continuum in hypertensive females.